The Influence Of Using Typing Master Application Media on 10 Finger Typing Skills in Office Technology Subjects at SMK Muhammadiyah 2 Sumberrejo Bojonegoro - Siti Fatimatuzzahroh; Durinta Puspasari (Institute of Computer Science (IOCS), 2021)
This research aims to analyze the effect of using typing master application media on 10 finger typing skill in Office Technology at SMK Muhammadiyah 2 Sumberrejo Bojonegoro. This research is a type of research with a quantitative approach. The population in this research is all students X grade of OTKP program which amounts 51 students. Data collection techniques in this research were closed questionnaires, interviews, and documentation. Instrument testing includes: instrument validity and instrument reliability. Data analyzed techniques used in this research include: classic assumption test includes normality test and heteroscedasticity test, and hypothesis test using simple linear regression test. The result of this research showed that the result of simple linear regression analysis for a significance value 0,000. Which the significance value is smaller or < 0,05. While the tcount value 7,707 and the ttable value 2,009. Which mean tcount > ttable or 7,707 > 2,009, can be concluded that the use of typing master application media has a significance effect on 10 finger typing skill.